2 0 1 8 exp ( ∫ 0 2 π cot ( x + 2 0 1 8 − 2 0 1 8 i ) d x ) = ?
Notations:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nope, buddy. This is a wrong solution. You are missing an isolated singularity of cot ( x ) and the value of the integral above is 2 π i . Here you can see a right solution before applications, very interesting too
Log in to reply
While not technically correct, it is essentially correct, since we do have ∫ cot ( x + Z ) d x = ln sin ( x + Z ) on any branch of the logarithm. In particular, since sin ( x + Z ) = 0 for all x ∈ [ 0 , 2 π ] , we know that ∫ 0 2 π cot ( x + Z ) d x = ln sin ( 2 π + Z ) − ln sin ( Z ) + 2 π i N = 2 π i N for some N ∈ Z ( N being the winding number for sin ( x + Z ) about 0 for 0 ≤ x ≤ 2 π ) Then the answer is 2 0 1 8 e 2 π i N = 2 0 1 8
Coincidentally, was there some vandalism on the wiki page? Most of the LaTeX functions are broken.
Edit: I don't know if the wiki page is abandoned, but I went ahead and cleaned up the LaTeX and layout so I could at least read what is there.
Problem Loading...
Note Loading...
Set Loading...
Let Z = 2 0 1 8 − 2 0 1 8 i for compactness. The above definite integral evaluates to:
∫ 0 2 π c o t ( x + Z ) d x = l n s i n ( x + Z ) ∣ 0 2 π = l n s i n ( 2 π + Z ) − l n s i n ( Z ) = l n ( s i n ( Z ) s i n ( 2 π + Z ) ) .
Completing the above expression now yields:
2 0 1 8 ⋅ e x p [ l n ( s i n ( Z ) s i n ( 2 π + Z ) ) ] = 2 0 1 8 ⋅ s i n ( Z ) s i n ( 2 π + Z ) ;
and since s i n ( Z ) is 2 π -periodic, we conclude s i n ( Z ) = s i n ( 2 π + Z ) and 2 0 1 8 ⋅ s i n ( Z ) s i n ( 2 π + Z ) = 2 0 1 8 .